Risk Factors for Stroke Events in Bahteramas Hospital, Southeast Sulawesi Province - Seniwati, Seniwati; Supodo, Timbul; Rahmawati, Rahmawati (Magister Kesehatan Universitas Mandala Waluya, 2023)
Background: Based on Stroke data in the Bahteramas Hospital of Southeast Sulawesi Province in 2019, there were 53 cases. In 2020 the number of stroke cases was 119 cases and in 2021 the number of stroke cases was 164 cases. The purpose of the study was to analyze the risk factors for Hypertension, DM, Cholesterol and Diet against the incidence of Stroke in the Bahteramas Hospital, Southeast Sulawesi Province. Methods: This study used a Case Control Study approach. The population numbered 136 people. The Study Sample totaled 68 of Stroke patients and 68 of patients who did not stroke. The sample technique is Simple Random Sampling. The data is processed using the Odds Ratio Test and logistic regression. Result: The results showed that hypertension is a risk factor with an OR value of 12,963, Diabetes Mellitus or OR value of 2,263, cholesterol OR value of 7,756 and a diet of OR value of 1,304. Regression tests showed that hypertension and cholesterol were the factors most at risk for stroke Conclusion: Hypertension, diabetes mellitus, cholesterol and diet are risk factors for the incidence of stroke in the Bahteramas Hospital, Southeast Sulawesi Province. The most dominant factors at risk for the incidence of stroke are hypertension and cholesterol.